Systematic Literature Review on the Influence of Religiosity on Investment Decisions and the Mediating Roles of Norms-Moral, and Prudence Risk - Jenisa Andini; Henrycus Winarto Santoso; Mintarti Ariani (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study explores the impact of religiosity on investment preferences, focusing on direct effects and mediation through moral norms and precautionary risk. A systematic literature review (SLR) was conducted using the PRISMA protocol, analyzing studies published between 2009 and 2025. The review demonstrates that religiosity significantly influences investment decisions through these two mechanisms. Moral norms play a crucial role in shaping investment choices, particularly for religiously driven investors, while precautionary risk leads more religious individuals to prefer safer investment options. Additionally, the study identifies key theories commonly employed in the literature, such as Social Identity Theory and Theory of Planned Behavior (TPB), while also highlighting underexplored theories that could further enhance understanding of how religiosity impacts investment behavior. These gaps suggest opportunities for future research to apply these theories, especially in contexts like Islamic finance or emerging markets, to deepen the understanding of the relationship between religiosity and investment preferences.